"Please Sir, can we play a game?" : transforming games teaching and coaching: a practitioner's perspective : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy at Massey University, Palmerston North, New Zealand - Slade, Dennis George (Massey University, 2018)
Over the last 30 years, traditional skill-based game teaching models have gradually been supplemented by instruction under an inclusive banner of Game Centred Learning (GCL) but more specifically, Teaching Games for Understanding (TGfU). This thesis uniquely examines from a practitioner’s perspective how the development of GCL and its dissemination occurred in New Zealand (NZ) 1945-2015. The multi-method approach establishes through a triangulation of data sources utilising a bricolage approach that the development was not mandated by educational policy but evolved through various combinations of insights from early luminaries in the field and visits to NZ by a key figure in the field (Rod Thorpe). Additionally, a new guard of Physical Educators in pre-service teacher education colleges in NZ were also significantly influential in the dissemination of GCL strategies as was a new socio-ecological perspective in PE syllabi (1999; 2007). An emergent autoethnographic documentation of the author’s role further informs this evolution of GCL and TGfU practices in NZ. Bourdieu’s concepts of habitus, practice and field are used as markers to signal change and record tensions that ultimately led to adoption of GCL practice in PE teaching and sport coaching in NZ. The thesis findings present implications for PE practitioners through innovative GCL approaches, associated with play, mastery learning and TGfU, that involves transforming play. It is concluded that at a practical and theoretical level, TGfU should be seen in a holistic experiential sense and integrated into PE programmes acknowledging its potential to contribute to and enhance citizenship. The final contribution to knowledge of this research is the presentation of a model of GCL designed to transform play.
Keywords: Sports; Study and teaching; Physical education and training; Sports for children; Study and teaching; Coaching; Student-centred learning; New Zealand; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education::Subject didactics